Foaming Effects, Interfacial Morphologies and Impact Toughness of Polypropylene Foam Composites Toughened by EOC-g-MAH - Yang, Jinian; Wang, Chuang (Asian Journal of Chemistry, 2014)
Polypropylene/short glass fiber (PP/SGF) and PP/SGF/ethylene-1-octene (EOC) foam composites, with maleic anhydride grafted EOC (EOC-g-MAH) as compatilizer and impact modifier, were prepared. The cellular structures, interfacial morphologies and impact toughness were investigated. Results show that EOC-g-MAH is preferred to improve the foaming effects of the sample. Also, it is confirmed to be an effective plasticizer in the PP/SGF foam composites. Moreover, the highest impact toughness is obtained by the case of EOC-g-MAH modified PP/SGF/EOC. SEM observation reveals that interfacial interaction between short glass fiber and matrix is enhanced and EOC-g-MAH also facilitates the compatibility of ethylene-1-octene and polypropylene.